Child healthcare nurses' encounters with parents whose child is overweight. (September 2019) - Harder, Maria; Andersson, Sara; Golsäter, Marie
Nurses in the Swedish child healthcare system can make a difference by offering support to parents of children who are overweight or at risk of becoming so. Still, research concerning these nurses' clinical practice when encountering parents whose child is overweight is inadequate. The aim of this study was to describe nurses' clinical practice when encountering parents of an overweight child. Data were collected through interviews with 10 nurses, and a content analysis approach was used. The nurses' clinical practice is described in relation to Olander's theory: Individualising actions, Creating a dialogue, Documenting, and Focusing on normality. This study adds knowledge about nurses' clinical practice in encounters with parents whose child is overweight. Also, it adds information on how an issue in a specific care situation may contribute to further understanding and use of an existing theory in caring science.